Between expertise and sociability: the contributions of foreign technicians to a regional agricultural industry (Mendoza, Argentina) (1880-1924) (Quinto Sol, 2020)
The inclusion of foreign specialists in the national State and their performance in economic and agro-industrial agencies were pointed out by historiography, although recent contributions are on provincial offices.Since the modernization of wine production (1885), there have been institutional initiatives to respond to this transformation. One of them, the hiring of foreign experts to provide "new and useful" knowledge for an industry that is seen as the economy engine but with few technical bases. In particular, the trajectories of agronomists and oenologists are reconstructed since they present certain peculiarities:  they are hired by the national State to work in the province, they do not register an ascending cursus honorum in the State but alternated with the private sector and guild entities. In that course, they configured themselves as authorized voices in adverse periods of the provincial economy, even from a critical position to wine regulation. The possession of technical knowledge became an instrument to link up with other discussion spaces, thus transcending still weak state structures for the formation and permanence of bureaucratic teams.
Keywords: State; knowledges; agroindustries; technicians